Prevalence and outcomes of unscheduled revisits within 72 hours of discharge from emergency department - Maharjan, Rony; Joshi, Arabind; Thapa, Ganesh (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Emergency Department (ED) revisit shortly after discharge not only increases the workload but also impacts healthcare cost and quality of patient care. The main aim of this study was to determine the rates, causes, and outcome of revisits within 72 h of ED.Method: A cross-sectional study over six months was carried out in the ED of Patan Hospital, Patan Academy of Health Science (PAHS). All patients who revisited an ED within 72 h of the initial visit were included. Variables studied were age-group, gender, chief complaints, diagnosis of initial and revisit. Study was ethically approved by the Institutional Review Committee of PAHS. Data were analyzed descriptively using MS Excel and SPSSversion20.Result: Out of 23,879 cases, 280(1.2%) revisited the ED within 72 h. Fever was the most common symptom accounting for 109(38.9%) patients of total revisit cases. In 190(67.9%) patients, the main reason for the visit was due to the symptoms not getting better. Around two-third i.e. 177(63.2%) of revisits were discharged and 103(36.8%) were admitted. Maximum revisits were found to be done among the 20-59y age group.Conclusion: The main reason for the revisit to ED was due to the persistence of the previous symptoms.